2022
DOI: 10.1155/2022/7359584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Repair and Reconstruction Methods Combined with Psychological Intervention on Quality of Life and Negative Emotion in Patients with Oral Cancer

Abstract: Objective. To explore the effects of different repair and reconstruction methods combined with psychological intervention on the quality of life and negative emotion of patients with oral cancer. Methods. 180 patients with oral cancer treated in our hospital from January 2018 to January 2020 were randomly divided into group A, group B, and group C, with 60 cases in each group. Group A and group B were repaired with submental island flap and free flap, respectively. Group C was divided into two groups, and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…These strategies have been demonstrated as the efficient ways to alleviate depressive and anxiety symptoms in cancer patients previously. 11 , 23 , 24 We adopted one-to-one communication to give the psychological intervention. It has been reported that one-to-one communication with patients could help encourage patients to express their negative emotions and transfer any positive energy.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies have been demonstrated as the efficient ways to alleviate depressive and anxiety symptoms in cancer patients previously. 11 , 23 , 24 We adopted one-to-one communication to give the psychological intervention. It has been reported that one-to-one communication with patients could help encourage patients to express their negative emotions and transfer any positive energy.…”
Section: Discussionmentioning
confidence: 99%